PROFESIONALITAS GURU SENI RUPA SMP NEGERI SE-KABUPATEN BATANG TAHUN 2014 - ARDIAN, SETIAJI (Eduarts: Jurnal Pendidikan Seni, 2015)
The researchers would like to discuss two issues, namely (1) How is professionalism Junior High School art teacher throughout Batang district? (2) What are the factors that influence the professionalism Junior High School art teacher throughout Batang District ?. The results showed that professionalism Junior High School art teacher throughout Batang district assessed by the principal, teachers of art, researchers, and students with the competencies assessed were pedagogic competence, professional competence, social competence, and personal competence included in either category. Based on the observation and analysis of researchers, there are several supporting factors and obstacles that affect the level of professionalism of teachers of art in Batang. Supporting factor is the educational background of teachers, teaching skills of each teacher, and the status of teachers who are certified professionals. In addition to supporting factors, there are also factors that hinder the teacher in the learning activities, among other limitations learning media, as well as the supporting infrastructure of subjects of art. The suggestion is: (1) Master the art should be able to always improve professionalism so that performance can be grown, (2) The school is expected to provide the necessary facilities for teachers and students to study art is going well, (3) Experts or education practitioners are expected to conduct further research. Keywords: Professional, Teacher , Visual Art .